3D inversion of total magnetic intensity data for time-domain EM at the Lalor massive sulphide deposit. Issue 2 (1st June 2017) - Yang, Dikun; Oldenburg, Douglas W.
Abstract : The Lalor deposit is a massive sulphide that is characterised as a stack of conductive ore lenses buried more than 600 m deep. We invert helicopter sub-audio magnetics (HeliSAM) data from Lalor collected using a ground large transmitter loop and an airborne total magnetic intensity (TMI) magnetometer measuring the time-domain electromagnetic (EM) responses. The TMI data are modelled as a projection of the anomalous field onto the earth's magnetic field. Inversion of these data is considered a significant case study because of two challenges. First, the early-time data are contaminated by the infrastructure on the surface. Second, inverting the data with a uniform half-space as the initial model results in a mathematically acceptable, but non-geologic, model. We create workflows to overcome these difficulties. For the contaminated data, we use a locally refined mesh and a constrained inversion to recover highly conductive cells near the surface that effectively represent the infrastructure. This allows us to safely extract geologic information from the early time data. The non-uniqueness in the inversion is reduced by warm-starting the voxel 3D inversion with a more reasonable initial guess, for example, a block model from geometric inversions. Those procedures greatly improve the inversion image from the surface to the bottom of the target at Lalor, and they can easily be incorporated into the industrial production workflows. Abstract : 3D voxel inversion of HeliSAM data at the Lalor massive sulphide deposit suffers from: (1) contamination of early-time data by the near-surface infrastructure and (2) creation of a mathematically acceptable but non-geologic model from inversion of late-time data. We propose a procedure that incorporates the infrastructure in our inversion, and a warm-start approach to overcome the non-uniqueness.